Efisiensi & Efektivitas Pengelolaan Dana Zakat di Lazismu Kota Pekalongan Periode 2019-2024 Dengan Metode: Data Envelopment Analysys (DEA) & Alocation To Collection Ratio (ACR) - Firda Septiyani; Fadli Hudaya (Jurnal Ilmiah Ekonomi Islam, 2026)
This study aims to analyze the efficiency and effectiveness of zakat fund management at Lazismu Pekalongan City during the 2019–2024 period. This study employs a descriptive quantitative approach. The data used are secondary data derived from the financial reports of Lazismu Pekalongan City for the years 2019–2024. Efficiency was measured using the Data Envelopment Analysis (DEA) method with Constant Return to Scale (CRS) and Variable Return to Scale (VRS) models, employing both input-oriented and output-oriented approaches. Meanwhile, effectiveness was measured using the Allocation to Collection Ratio (ACR). The research results show that during most of the observation period at Lazismu Pekalongan City, efficiency levels reached 100%, specifically in 2019, 2020, 2021, and 2023. However, in 2022 and 2024, inefficiencies persisted, with efficiency values of 85.1% and 46.4%, respectively, in the CRS model. In the VRS model, inefficiency occurred only in 2024, with an efficiency value of 52.7% in the input-oriented approach and 81.6% in the output-oriented approach. Meanwhile, the results of effectiveness measurement using the ACR ratio indicate that Lazismu Pekalongan City performance falls within the effective to highly effective category, with ACR values ranging from 81% to over 100%.